The Impact of Self Confidence on Student Discussion Activeness of PAI IAIN Palangka Raya - Mazrur Mazrur (Departement of Mathematics Education, 2023)
Activeness in the lecture process will help students understand the course of lectures. For this reason, as prospective teacher students, they are required to be able to have self-confidence so that in the lecture process they will be able to be actively involved in a discussion and in the future when they graduate they will be able to become teachers who are able to build student motivation. The purpose of this research is the impact of self-confidence on active discussion during lectures. The method used in this research is descriptive qualitative with the subject of class 2019 students. The results of this study indicate that students who have confidence in their lectures will actively discuss boldly expressing opinions, communicate clearly and have motivation to excel.